Health impact assessment of major collective events: an overview of the available experiences (Epidemiology, Biostatistics, and Public Health, 2022)
Background: major sporting and cultural events are a sensitive political and social issue. The aim of this study was to perform a critical review of the international literature regarding health impact assessment (HIA) studies of major events to identify all the health indicators available in the literature.Methods: we drew up a review of available literature on HIAs pertaining to major sports and cultural events. The papers obtained were read and then assessed in relation to the inclusion criteria, and the health indicators used were listed and commented upon.Results: we found three published HIA reports. One is a full report, and the other two are a screening report and a rapid HIA report. Through a detailed analysis, it has been possible to develop a set of indicators that can be used for future HIAs on major sporting and cultural events.Conclusions: reports of HIAs for major events that are available online identify several health impacts. In the pre-event phase, negative effects are predominant; in the post-event period, positive impacts prevail. The characteristics of the different stakeholders involved in the events play an important role in the evaluation process.